(untitled) (Nativa, 2020)
Objetivou-se avaliar as alterações químicas ao longo do perfil do solo, o desenvolvimento e a produtividade da cultura da soja (Glycine Max L. “Merr”) em função da aplicação superficial de silicatos na correção da acidez do solo. Este experimento vem sendo conduzido há sete anos, em delineamento com blocos casualizados e parcelas subdivididas. As parcelas foram distribuídas inicialmente pelas formas de aplicação dos corretivos: aplicação com incorporação até 20 cm de profundidade e aplicação em superfície; e na subparcela têm se os corretivos: escória de aciaria, escória de forno de panela, escória do aço, wollastonita, calcário agrícola e calcário agrícola calcinado; além de uma testemunha sem aplicação de material corretivo; com quatro repetições. Os corretivos foram reaplicados manualmente a lanço, sem incorporação para ambas as formas de aplicação adotadas na implantação do sistema plantio direto. A wollastonita, escória do aço inox e escória de aciaria aumentaram os teores de P, K, Ca e Si, e os valores de SB, V% e pH. Para a soja, esses acréscimos foram fundamentais para proporcionar incrementos na produtividade de grãos chegando a 7,0 Mg ha-1 com a aplicação de escória de aciaria, não diferindo estatisticamente da escória do aço inox e da wollastonita. Palavras-chave: acidez do solo; calagem; escória de siderurgia; silício; soja. CHANGES IN THE SOIL-PLANT SYSTEM DUE TO THE REAPPLICATION OF SILICATES IN THE NO-TILLAGE SYSTEM ABSTRACT: The objective of this study was to evaluate the chemical changes along the soil profile, development and yield of the soybean crop (Glycine Max L. "Merr") as a function of the superficial application of silicates in soil acidity correction. This experiment has been conducted for seven years, in a randomized complete block design and subdivided plots. The plots were initially distributed by the application of the correctives: application with incorporation up to 20 cm and surface application; and in the subplot have the correctives: steel slag, ladle furnace slag, stainless steel slag, wollastonite, agricultural limestone and calcined agricultural limestone; as well as a control treatment without the use of correctives; with four replicates. The correctives were reapplied manually, without incorporation for both forms of application adopted in the implantation of the no-tillage system. Wollastonite, stainless steel slag and steel slag increased the contents of P, K, Ca and Si, and the values of SB, base saturation and pH. For soybeans, these additions were essential to provide grain yield increases of 7.0 Mg ha-1 with the application of steel slag, not statistically differing from stainless steel slag and wollastonite. Keywords: acidity of soil; liming; steel slag; silicon; soybean.